2020
DOI: 10.1016/j.ajpath.2019.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal SIRT1 Deficiency Protects Mice from Ethanol-Induced Liver Injury by Mitigating Ferroptosis

Abstract: Aberrant liver sirtuin 1 (SIRT1), a mammalian NAD þ-dependent protein deacetylase, is implicated in the pathogenesis of alcoholic liver disease (ALD). However, the role of intestinal SIRT1 in ALD is presently unknown. This study investigated the involvement of intestine-specific SIRT1 in ethanol-induced liver dysfunction in mice. Ethanol feeding studies were performed on knockout mice with intestinal-specific SIRT1 deletion [SIRT1i knockout (KO)] and flox control [wild-type (WT)] mice with a chroniceplusbinge … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
67
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 44 publications
2
67
0
1
Order By: Relevance
“…More importantly, depletion of SIRT1 has been reported to exacerbate I/R injury in aged livers (Chun et al, 2018). Furthermore, studies have shown that reduced intestinal expressions of SIRT1 can protect mice against alcohol-induced liver injury by reducing ferroptosis (Zhou et al, 2020). Based on the aforementioned literature, we proposed a hypothesis that USP22/SIRT1 axis may play pivotal roles in ferroptosis-induced cardiomyocyte death, and sought to define its roles in an animal model of MI/R and a cellular model of IR in cardiomyocytes, hoping to highlight a novel targeting approach to MI/R therapy.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly, depletion of SIRT1 has been reported to exacerbate I/R injury in aged livers (Chun et al, 2018). Furthermore, studies have shown that reduced intestinal expressions of SIRT1 can protect mice against alcohol-induced liver injury by reducing ferroptosis (Zhou et al, 2020). Based on the aforementioned literature, we proposed a hypothesis that USP22/SIRT1 axis may play pivotal roles in ferroptosis-induced cardiomyocyte death, and sought to define its roles in an animal model of MI/R and a cellular model of IR in cardiomyocytes, hoping to highlight a novel targeting approach to MI/R therapy.…”
Section: Introductionmentioning
confidence: 99%
“…21 Activated inflammasomes actlvate caspase 1/11, which mature GSDMD and pro-, IL-1β and pro-IL-18, resulting in release of DAMPs, IL-1β and IL-18 [30][31][32] Reactive hydroxyl radical by iron accumulation injures lipid membranes to induce lipid peroxidation and membrane instability, which can ultimately result in leakage of cellular material and cell death. [38][39][40][41][42][43] The role in or to immune cells Kupffer cells produce TNFα by LPS-TLR4 signal activation from leakage-gut. 5 Immune cells are activated by DAMPs released from necroptotic hepatocytes 5,[14][15][16] Autophagy plays a role of anti-inflammatory response and anti-steatosis via cannabinoid receptor 2 in Kupffer cells.…”
Section: Release Of Damps 36mentioning
confidence: 99%
“…Accumulating evidence suggests that ferroptosis is a novel type of PCD in liver diseases including ALD. [39][40][41][42] Hepatic iron accumulation is causally linked with chronic alcohol consumption, and it also contributes to hepatic inflammation and development of HCC in ALD. 43,44 Iron accumulates in response to ethanol, at least in part due to increased expression of hepcidin, a 25 amino-acid peptide, primarily expressed in hepatocytes, that is secreted from the liver in response to increased H 2 O 2 concentrations in liver.…”
Section: Ferroptosismentioning
confidence: 99%
See 1 more Smart Citation
“…Dysregulation of ferroptosis is observed in a wide range of pathological conditions, including chronic pulmonary obstructive disease, intracerebral hemorrhage, degenerative diseases, acute kidney injury, and cancer 2,[9][10][11][12] . Accumulating evidence has addressed that blockage of ferroptosis can mitigate the development and progression of a number of liver diseases, including hemochromatosis, immune-mediated hepatitis, alcoholic steatohepatitis, and acute liver failure ( Fig.2 and Table 1) [13][14][15][16] . Nonetheless, in some circumstance, induction of ferroptosis may be beneficial for adjusting drug resistance and contributing to combined treatment regimens against hepatocellular carcinoma (HCC) [17][18][19] .…”
Section: Introductionmentioning
confidence: 99%